Effect of carbamide peroxide bleaching agents on the physical properties and chemical composition of enamel - (:unkn) unknown (MOSHER & LINDER, INC, 2001)
Purpose: To evaluate the effect of two commercially available carbamide peroxides bleaching agents, Opalescence and Nite-White, in concentrations of 10, 15 and 16%, on enamel. Materials and Methods: Vickers hardness measurements (VH) were made at the surface and 110 mum below the surface on human enamel samples that were treated for 5 or 10 days, 6 hrs/day. Furthermore, infrared spectrophotometry (IR), Fourier transform infrared spectrophotometer (FTIR) and X-ray diffraction (XRD) measurements were performed after the VH measurements were completed. Results: Using a one-way ANOVA, statistically significant differences in VH could be established between surface and subsurface VH values. For all groups, including the control group, the surface VH values were statistically significantly higher than subsurface VI-I. IR, FTIR and XRD established a change from hydroxyapatite to primary calcium ortho phosphate [Ca(H2PO4)(2)] for all experimental groups except for 10% Opalescense tested for 5 or 10 days.